THE INFLUENCE OF WATERFALL DISTANCE ON BRYOPHYTES DIVERSITY IN THE COBAN RONDO WATERFALL AREA, PUJON, MALANG - Salsabila Rofifah; Ilmiatunnisa, Rahmatin; Hakimah, Wardatul; Tias, Anggi Kusumaning; Rahmawan, Agus Rizki Dwi; Agustin, Dhiva Ayu; Fardhani, Indra (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2024)
Bryophytes is one of the various plant groups that have an important role in biodiversity. Bryophytes have an essential role in environmental ecology, including mosses contributing to the nutrient and water cycle and the carbon exchange cycle. This research aims to determine the effect of waterfall distance on bryophyte diversity in the waterfall area. This research uses an exploratory descriptive method with data collection locations at Coban Rondo Waterfall, Pujon District, Malang Regency. The research was carried out by collecting data directly in the field by observing and exploring according to the conditions at the research location. The objects in this research are classes bryophytes that grow around the waterfall area by creating three plots measuring 5m x 5m with the installation at the wet zone which is located in the waterfall area <25 m, the humid zone which is 25-50 meters from the waterfall, and the dry zone which is more than >50 meters from the waterfall. Each bryophyte found in a single plot in three zones will be analyzed by considering the factors of temperature, humidity, light intensity, and soil pH. The results of the study showed that there was an influence of waterfall distance on bryophyte diversity. The closer the location where bryophytes grow to a waterfall, the more diverse the number of species.